2018
DOI: 10.1186/s12885-018-5025-y
|View full text |Cite
|
Sign up to set email alerts
|

Sleep duration and the risk of cancer: a systematic review and meta-analysis including dose–response relationship

Abstract: BackgroundThe effect of sleep duration on cancer risk remains controversial. We aimed to quantify the available evidence on this relationship using categorical and dose–response meta-analyses.MethodsPopulation-based cohort studies and case-control studies with at least three categories of sleep duration were identified by searching PubMed, EMBASE, and the Cochrane Library database up to July 2017.ResultsSixty-five studies from 25 articles were included, involving 1,550,524 participants and 86,201 cancer cases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
123
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(132 citation statements)
references
References 95 publications
7
123
1
1
Order By: Relevance
“…However, a study from the US did not find an association with cancer mortality [ 30 ]. Because sleep duration may be differentially associated with specific cancer types [ 9 ], the variation in results across geographic regions may be partly due to the distribution of specific cancer deaths in the population. Given the limited number of cancer deaths, we were not able to investigate the associations by different cancer types in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a study from the US did not find an association with cancer mortality [ 30 ]. Because sleep duration may be differentially associated with specific cancer types [ 9 ], the variation in results across geographic regions may be partly due to the distribution of specific cancer deaths in the population. Given the limited number of cancer deaths, we were not able to investigate the associations by different cancer types in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that poor quality and quantity of sleep may have negative health effects. Both short and long sleep are associated with increased risks of type 2 diabetes [ 7 ], cardiovascular disease (CVD) [ 8 ], and certain types of cancer [ 9 , 10 ]. Short sleep, in particular, has been associated with alteration in glucose metabolism, upregulation of appetite [ 6 ], and increased levels of C-reactive protein (a pro-inflammatory marker) [ 11 ] and carotid intima-media thickness (atherosclerosis indicators) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have explored the association between sleep duration, one aspect of sleep quality, and prostate cancer risk but with mixed results. The most recent meta‐analysis by Chen et al 8 including these amongst 65 studies total revealed that neither short nor long sleep duration was associated with increased overall cancer risk. Four studies examining prostate cancer risk were included in this meta‐analysis and when summarized, no association was shown between either short sleep duration (defined as <7 hours of sleep per night; OR: 0.95; 95% CI: 0.86‐1.04) or long sleep duration (defined as >9 hours of sleep; OR: 0.75; 95% CI: 0.54‐1.05) and prostate cancer risk 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of sleep quality and sleep disruption has been examined in other diseases, the role of sleep quality and disruption in cancer and specifically, prostate cancer, is not well understood. A meta‐analysis by Chen et al 8 found that sleep duration was not significantly associated with overall cancer risk, while a meta‐analysis by Lu et al 9 found longer sleep duration was positively associated with colorectal cancer, but inversely associated with prostate cancer 8,9 . A study by Flynn‐Evans et al 10 found a strong positive association between shift work and elevated prostate‐specific antigen (PSA) levels in men without prostate cancer, 10 while studies by Parent et al 11 and Kubo et al 12 found an elevated risk of prostate cancer in association with night‐shift work, supporting a possible role for sleep quality and disruption in prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Results from meta-analyses on the association of sleep duration with breast cancer risk are inconsistent [16,17]. While a 2017 meta-analysis reported a non-linear association between sleep duration and breast cancer risk, a 2018 categorical meta-analysis of sleep duration and cancer risk did not find an association of breast cancer risk for short and for long sleep, versus average sleep duration, in a subgroup analysis [16,17]. However, both meta-analyses did not differentiate between results from studies with prospective and retrospective study designs.…”
Section: Introductionmentioning
confidence: 99%